2017
DOI: 10.1111/dme.13320
|View full text |Cite|
|
Sign up to set email alerts
|

A population‐based study of the association between dysglycaemia and hearing loss in middle age

Abstract: There was progressively increasing mid-range hearing loss with worsening glucose tolerance in younger individuals, suggesting dysglycaemia-associated early-onset presbycusis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Among these examined frequencies, significant differences were found between the young, middle and old groups for PTA (p<0.001), confirming that the hearing threshold increases with age, both in males and females 18. Furthermore, Sommer et al reported that a 1-year increase in age would raise the risk of hearing loss by 15% 14…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Among these examined frequencies, significant differences were found between the young, middle and old groups for PTA (p<0.001), confirming that the hearing threshold increases with age, both in males and females 18. Furthermore, Sommer et al reported that a 1-year increase in age would raise the risk of hearing loss by 15% 14…”
Section: Discussionmentioning
confidence: 67%
“…We computed the pure-tone average (PTA) at speech frequencies (0.5, 1, 2 and 4 kHz; speech-PTA) and high frequencies (3, 4, 6 and 8 kHz; high-PTA) 12. Hearing loss was defined as speech-PTA of ≥26 dB in the better ear,9 which is consistent with the WHO definition of clinically significant hearing loss,13 and this can identify patients with bilateral hearing loss and related functional impairments 14…”
Section: Methodsmentioning
confidence: 93%
“…In the NHANES and in a study by Sommer et al ,9 hearing impairment was more prevalent among adults with diabetes in a multivariable analysis. It is in contrast to our study where neither diabetes nor blood concentrations of glucose were significantly correlated with hearing loss (online supplementary table 1).…”
Section: Discussionmentioning
confidence: 80%
“…Despite its importance for public health, the prevalence of hearing loss and its associated factors has not been widely investigated worldwide 2–11. For many countries, data on the prevalence of hearing loss are not yet available, and the factors associated with hearing loss have not been examined in a detailed manner.…”
Section: Introductionmentioning
confidence: 99%
“…In an article by Sommer et al , the author name C. G. Brenann‐Jones is incorrect and should be listed as C. G. Brennan‐Jones. Therefore the correct author list is:…”
mentioning
confidence: 99%